Health Care Markets, the Safety Net, and Utilization of Care among the Uninsured - Gresenz, Carole Roan (Blackwell Science Inc, 2007)
OBJECTIVE: To quantify the relationship between utilization of care among the uninsured and the structure of the local health care market and safety net. DATA SOURCES/STUDY SETTING: Nationally representative data from the 1996 to 2000 waves of the Medical Expenditure Panel Survey (MEPS) linked to data from multiple secondary sources. STUDY DESIGN: We separately analyze outpatient care utilization and whether an individual incurred any medical expenditure among uninsured adults living in urban and rural areas. Safety net measures include distances between each individual and the nearest safety net providers as well as a measure of capacity based on local government and hospital health expenditures. Other covariates include the managed care presence in the local health care market, the percentage of individuals who are uninsured in the area, and local primary care physician supply. We simulate utilization using standardized predictions. PRINCIPAL FINDINGS: Distances between the rural uninsured and safety net providers are significantly associated with utilization. In urban areas, we find that the percentage of individuals in the area who are uninsured, the pervasiveness and competitiveness of managed care, the primary care physician supply, and safety net capacity have a significant relationship with health care utilization. CONCLUSIONS: Facilitating transport to safety net providers and increasing the number of such providers are likely to increase utilization of care among the rural uninsured. Our findings for urban areas suggest that the uninsured living in areas where managed care presence is substantial, and especially where managed care competition is limited, could be a target for policies to improve the ability of the uninsured to obtain care. Policies oriented toward enhancing funding for the safety net and increasing the capacity of safety net providers are likely to be important to ensuring the urban uninsured are able to obtain health care.